A bright and moisture-resistant red-emitting Lu3Al5O12:Mn4+, Mg2+ garnet phosphor for high-quality phosphor-converted white LEDs. Issue 34 (16th August 2017) - Chen, Yibo; Wu, Kuanglun; He, Jin; Tang, Zhengbin; Shi, Jianxin; Xu, Yiqin; Liu, Zhao-Qing
Abstract : MgF2 assisted delicate synthesis and application of a bright and moisture-resistant LAG:Mn 4+, Mg 2+ phosphor. Abstract : The rational and delicate synthesis of Mn 4+ activated red-emitting oxide phosphors with high photoluminescence quantum yield (PLQY) and photo-stability for developing high-quality w-LEDs still remains a great challenge. Herein, we demonstrate a simultaneous ion co-substitution design strategy to synthesize a red-emitting Lu3 Al5 O12 :Mn 4+, Mg 2+ garnet phosphor delicately with the assistance of MgF2 . The Mn 4+ activated garnet phosphor exhibits superior moisture resistance properties and high PLQY ( ca. 72.41%), which emits a bright and narrow-band red light peaking at ∼670 nm due to the 2 E– 4 A2 spin-forbidden transition of Mn 4+ upon UV excitation. Remarkably, MgF2 as a charge compensator & flux can not only accelerate the solid state reaction, but also greatly improve the emission intensity. Furthermore, by employing the as-prepared Lu3 Al5 O12 :Mn 4+, Mg 2+ as a red component, we fabricate a warm w-LED with a high color rendering index ( R a = 81.4) and low color temperature (CCT = 4766 K) based on a UV chip and commercial blue and yellow phosphors.